In Vitro Immunomodulatory Effects of Inonotus obliquus Extracts on Resting M0 Macrophages and LPS-Induced M1 Macrophages. (21st April 2022) - Shen, Dayue; Feng, Yating; Zhang, Xilan; Liu, Jing; Gong, Le; Liao, Hui; Li, Rongshan
Abstract : Background . Inonotus obliquus (Chaga) is a parasitic fungus that is distributed mainly in northeast China. Our literature research showed chaga polysaccharides have bilateral effects on tumor necrosis factor (TNF)- α and interleukin (IL)-1 β levels when they exert antitumor and antidiabetic activities. The current research tried to explore the influence of chaga extracts on inflammatory factors via macrophage polarization which has bilateral immune-regulation not only on healthy tissue homeostasis but also on pathologies. Methods . Chaga was extracted with 100°C water and precipitated with 80% ethanol. The extracts were studied on RAW264.7 macrophage at resting condition (M0) and lipopolysaccharide (LPS)-activated subtype (classic activated macrophage, M1). The IL-1 β, TNF- α, nitric oxide (NO) level, and the protein expressions of M1 and alternative activated macrophage (M2) markers including IL-1 β, inducible NO synthase (iNOS), mannose receptor (CD206), and arginase (Arg)-1 were compared. Results . The 100 g extracts contained 13.7 g polysaccharides and 1.9 g polyphenols. Compared with M0, the 50  μ g/mL extracts increased NO level (P < 0.05 ) and decreased CD206 and Arg-1 expression significantly (P < 0.05 ). The extracts at 100–200  μ g/mL increased NO and TNF- α level (P < 0.05 ), but increased iNOS and IL-1 β expression significantly (P < 0.05 ). Compared with M1, the extracts decreased NO level at 25, 50, 100, and 200  μ g/mL and decreased IL-1 β and TNF- α level at 100–200  μ g/mL significantly (P < 0.05 ). At 25–200  μ g/mL, the extracts significantly increased CD206 and Arg-1 expression and decreased IL-1 β and iNOS expression separately (P < 0.05 ). Conclusions . Our research suggested that the bilateral effects of the chaga extracts on iNOS, IL-1 β, and NO level on M0/M1 macrophages might be related with chaga polysaccharides and chaga polyphenols. Some in vivo anticancer and antidiabetic research of purified chaga polysaccharides related to macrophage differentiation should be conducted further.